Vivienda Amazonica - Centro de Estudios Teológicos de la Amazonía (CETA) (My University, 1900)
SPANISH: Se observo una vivienda amazonico con diseño de dos casas una detras de otra, donde la parte delantera funciona como sala y la parte trasera funciona como cocina con barandas tipos cruzadas, techo de hoja de irapay y paredes de maderas.
ENGLISH: An Amazonian house with a design of two houses one behind the other was observed, where the front part functions as a living room and the rear part functions as a kitchen with crossed type railings, an irapay roof and wooden walls

SPANISH: Se observo una vivienda amazonico con diseño de dos casas una detras de otra, donde la parte delantera funciona como sala y la parte trasera funciona como cocina con barandas tipos cruzadas, techo de hoja de irapay y paredes de maderas.
ENGLISH: An Amazonian house with a design of two houses one behind the other was observed, where the front part functions as a living room and the rear part functions as a kitchen with crossed type railings, an irapay roof and wooden walls
Amazon Housing
Keywords: Houses--Peru|~|Rural Infrastructure--Housing--Peru|~|Houses|~|Iquitos (Perú)|~|Casas|~|Perú|~|Estructura Rural|~|Viviendas|~|Perú|~|Casas|~|Iquitos (Perú)|~|Houses|~|Peru|~|Rural Infrastructure|~|Housing|~|Peru|~|Houses